SENI LUKIS WAYANG KOPANG PERSPEKTIF PENDIDIKAN SENI RUPA HINDU - I Kadek Sumadiyasa; I Wayan Arissusila; I Putu Gede Padma Sumardiana; Ni Luh Putu Trisdyani (UNHI PRESS, 2021)
Kopang Puppet Art Painting in Kopang Workshop Kerambitan Village Tabanan Regecy is a work of fine art education and Hindu ornament which is very unique that was inherited traditionally. It is uniquely researched with title Kopang Puppet Art Painting Perspective of Hindu Fine Art Education. With problem, 1) How are the form, function and values of Fine Art education and Hindu Ornaments in it. The result of research analysis found about how is the form of Kopang puppet art painting in Kerambitan village Tabanan that is the form of puppets for Human, God and Goddesses, animal, giant, etc. In the form of tall and big/Landung which consist of 3 parts such as Main (Head of puppet), Madya/Body of the puppet, Nista/Foot of the puppet), With Flat Symmetrical Balanced Composition Arrangement, Simple Dark Color. Materials and tools; canvas, brush, pencil, Ornaments; simple. Process; sketch, ngorten, coloring, nyawi, decorating. The function of Kopang puppet art painting; Religion as Srada Bakti, Culture as classic fine art preservation, Education as character education of Hindu fine art, as well as functioned as identity. The educational values of fine art and Hindu ornaments in Kopang puppet art painting; Educational, sincerity, creativity, unity values.